(3GdEMUGA aj GdJQHjI (B/s - (3CHh eZdj, hGFds; (3YHOGdMGaX, SdGeI s ((3YeGf(B: s (3GdjGRhQj(B, s, 2007)
(3jMJhj Ydi ebOeI dOQGSGJ GdGMUGA aj GdJQHjI, JeKjd GdHjGfGJ aj LOGhd hJhRjYgG GdJcQGQj, ebGjjS GdfRYI GdeQcRjI hebGjjS GdJTJJ, GdGQJHGW hGdGfMOGQ, GdJhRjYGJ GdeLJeYjI GdGMJeGdjI hGdJhRjYGJ GdYjfjI, JbOjQ eYGde GdeLJeY HGSJNOGe YjfI hGMOIs
(3GdedGMb U(B.207 (3; GdeQGLY U(B.205s
Keywords: (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdJQHjI(B- (3GdWQb GdEMUGFjIs